Covenants and Collateral as Incentives to Monitor. - Rajan, Raghuram; Winton, Andrew (Journal of Finance, 1995)
Although monitoring borrowers is thought to be a major function of financial institutions, the presence of other claimants reduces an institutional lender's incentives to do this. Thus loan contracts must be structured to enhance the lender's incentives to monitor. Covenants make a loan's effective maturity, and the ability to collateralize makes a loan's effective priority, contingent on monitoring by the lender. Thus both covenants and collateral can be motivated as contractual devices that increase a lender's incentive to monitor. These results are consistent with a number of stylized facts about the use of covenants and collateral in institutional lending.